ENaC regulation by proteases and shear stress - Shi, Shujie (2013)
Epithelial Na(+) channels (ENaCs) are comprised of subunits that have large extracellular regions linked to membrane spanning domains where the channel pore and gate reside. A variety of external factors modify channel activity by interacting at sites within extracellular regions that lead to conformational changes that are transmitted to the channel gate and alter channel open probability. Our review addresses two external factors that have important roles in regulating channel activity, proteases and laminar shear stress.